Determinación de la co-inoculación con microorganismos rizosféricos en el cultivo de la papa (Solanum tuberosum L) variedad bolona - Agila Hidalgo, Silvana Gabriela (2016)
The cultivation of potato (Solanum tuberosum L.) is one of the most important food worldwide. In Ecuador is the main food of the Andean populations especially for their energy and nutritional content. Agrochemical applications to increase agricultural yields are very high, affecting the economy of the farmer and soil pollution. This requires generating alternative agricultural production using sustainable methods and one of them is the use of fixing microorganisms promoters nitrogen plant growth (PGPR) which are used for the manufacture of known biological products as inoculants which can fix double nitrogen that favor the maintenance of soil fertility. This research "DETERMINATION OF CO - INOCULATION WITH MICRO rhizosphere GROWING POTATO (Solanum tuberosum L.) VARIETY BOLOGNA " was performed at the Laboratory of Biotechnology in order to know the efficiency of the rhizosphere microorganisms on growth plant by in- tests vitro analyze rhizobacteria to determine the production of indole acetic acid (IAA) and solubilization of phosphorus, Sphingomonas sanxanigenens isolated is the one that produces the greatest amount of AIA with a value of 1.784 ug ml -1 , followed by Azotobacter vinelandii and Ralstonia sp, 0.185 and with values of 0.136 ug ml - 1 in 72 hours respectively AIA , the isolated Penicillium sp + Sphingomonas sanxanigenens . He solubilized fosforo showing the formation of a halo of 5,06cm. In addition the co- inoculation was made with rhizosphere microorganisms where the effect on plant growth under controlled conditions, where an effective response to strains Ralstonia sp was observed was evaluated + Penicillium sp and Sphingomonas sanxanigenens + Penicillium sp presenting data height of 130 cm and 107cm respectively, ie, they had a beneficial effect on the potato plant in terms of promoting growth and increased biomass formation both radical and leaf.